FAKTOR YANG MEMPENGARUHI OPINI AUDIT GOING CONCERN - Carolina, Cyntia; Kusmila, Zesmi (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
The aim of this research is to determine the factors that influence going concern audit opinions on manufacturing companies listed on the Indonesian Stock Exchange in 2020-2022. The population in this research is manufacturing companies listed on the Indonesian Stock Exchange in 2020-2022 with the sample method used, namely purposive sampling and 66 companies were obtained in this research, a total of 198 companies over 3 years. The analysis technique used in this research is logistic regression. The data collection method uses a qualitative method with the type of data used being secondary data. This research variable was measured using dummy variables, while data analysis used SPSS 20. The results of this research show that there is a significant influence between audit tenure and previous year's audit opinion on the acceptance of going concern audit opinions in manufacturing companies listed on the Indonesian Stock Exchange in 2020 -2022